Diarrhea Prevention Counseling for Grade 4 and 5 School Students - Ristiana, Niken; Cahaya kusuma, Nur; Nurlinawati, Nurlinawati (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2023)
Diarrhea is a disease which if not treated properly can cause sudden loss of fluids and electrolytes, so that various complications can occur including dehydration, hypovolemic shock, organ damage and even coma. The most severe threat posed by diarrhea is dehydration which can lead to death, therefore the incidence of diarrhea is a health problem whose occurrence needs to be suppressed. The type of research used in this research is "One Groups Pretest-Posttest Design", which is a type of research that is pre-experimental design with pretest and posttest, where observations are made 2 (two) times before and after implementation. Therefore, Thus, the results obtained can be known more accurately, because they can be compared with before being given treatment and after being given treatment. Where the students who were the targets of this activity were student representatives from grade 4 and grade 5 with a total of 35 students. From the results of the research that has been done, it was found that there was an increase in students' knowledge of prevent diarrhea US a preventive measure in groups of elementary school children against the risk of getting diarrhea. With an average pre-test score of 45.71 and a post test average of 64. Provision of counseling on diarrhea prevention to students in grades 4 and 5 of SDN No. 205/IV Natural Barajo District Jambi has an influence on student knowledge.